Adherence of multi-micronutrient supplementation and hemoglobin level in children from 6 to 36 months of Huanca Huanca district, Peru, 2017 - Tinoco Ramos, Andrea (2018)
Objective: of the study was to determine the factors of adherence to supplementation with multimicronutrients related to the level of hemoglobin in children from 6 to 36 months of age in the district of Huanca Huanca, Huancavelica. Material and methods: the study was quantitative, non- experimental, correlational and transversal design approach. The sample was not probabilistic of intentional type, using the inclusion and exclusion criteria, and consisted of 60 children from 6 to 36 months of age. The instrument used for the data collection was the adhesion test for multimicronutrient supplementation from Espichan (2013) and the hemoglobin measurement was performed with Hemocue 201. Results found that 53.3% of the mothers had an average adherence. 53.3% of the children had normal hemoglobin. In addition, there is no relationship between the general adherence to multimicronutrient supplementation and the hemoglobin level, with a p-value of 0.385 and a low correlation was found in the factor related to the supplement with a p-value of 0.042. Conclussion: that both variables are not related.